2013
DOI: 10.1007/s12088-013-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacillus amyloliquefaciens SC06 Prevents Bacterial Translocation in Weaned Mice

Abstract: Probiotic is a preparation containing microorganisms that confers beneficial effect to the host. This work assessed whether oral administration of Bacillus amyloliquefaciens SC06 (Ba) could decrease bacterial translocation in weaned mice. Weaned C57BL/6 were randomly allocated into three groups: group I as the control group, group II were treated with 0.85 % NaCl. Group III was administered with probiotic Ba 1 9 10 9 CFU/day dissolved in 100 ll of 0.85 % NaCl for 30 days. Mice were then sacrificed, and tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Lei et al confirmed that the addition of different doses of Bacillus amyloliquefaciens in the diet significantly improved the overall growth performance and morphology of small intestine and increased the number of lactobacilli in the cecum ( 41 ). Ji, Hu, and Li reported that Bacillus amyloliquefaciens SC06 significantly increased the daily weight gain and reduced the diarrhea rate of weaned piglets in vivo ( 26 ). In our study, TL106 and antibiotics significantly increased the bodyweight of piglets at 7 and 14 days after weaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lei et al confirmed that the addition of different doses of Bacillus amyloliquefaciens in the diet significantly improved the overall growth performance and morphology of small intestine and increased the number of lactobacilli in the cecum ( 41 ). Ji, Hu, and Li reported that Bacillus amyloliquefaciens SC06 significantly increased the daily weight gain and reduced the diarrhea rate of weaned piglets in vivo ( 26 ). In our study, TL106 and antibiotics significantly increased the bodyweight of piglets at 7 and 14 days after weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Yongtao brings to light that the addition of B. amyloliquefaciens probiotics to the prenatal diet of pregnant sows promoted the production of short-chain fatty acids (SCFAs) in the intestines of both sows and newborn piglets with the improvement of their intestinal flora ( 24 ). Moreover, the oral administration of B. amyloliquefaciens SC06 can reduce bacterial translocation and affect the intestinal immune function in weaned mice ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…in a broiler CDI model where B. amyloliquefaciens did not confer protection to the in vivo model but showed significant anti-CD activity in in vitro experiments [ 56 ]. However, several previous studies reported that B. amyloliquefaciens successfully conferred protection against C. Difficile-associated disease in a mouse model [ 57 - 59 ]. The difference in physiology and infection surface area between hamsters and mice might be the reason for the observed variation in B. amyloliquefaciens efficacy, as was previously proposed for auranofin [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Bacillus amyloliquefaciens can be used as a probiotic in animal-healthy production. 24 Our previous work implied that Bacillus amyloliquefaciens SC06 (SC06) protected mice from HFD-induced obesity and liver injury via regulating the host metabolism and intestinal microbiota. 25 Hence, in order to investigate the mechanisms by which Bacillus reduces obesity in more detail, we explored the role of the probiotic Bacillus amyloliquefaciens SC06 in reshaping the intestinal microbial composition and changing metabolites and focused on the effects on bile acid metabolism in male ob/ob C57BL/6J mice as genetic obesity models.…”
Section: Introductionmentioning
confidence: 99%